Kinetics of Organic Matter thermal transformation in source rocks: Overview of Methods and Experimental results - M. Spasennykh; V. Shirokova; A. Ilmenskii; E. Kozlova; T. Bulatov; A. Goncharova; E. Leushina (Georesursy, 2024)
The paper is devoted to kinetic studies of thermal decomposition of organic matter in organic-rich rocks. Kinetic studies are the consisting part of geochemical investigations of source rocks and petroleum systems. The results are required for petroleum generation prediction and assessment of reservoir hydrocarbons quantity and quality using basin modelling. Kinetic data is also applied for simulation of in-situ kerogen conversion and hydrocarbons generation, which are the main processes of thermal methods of enhanced oil recovery (thermal EOR).The paper summarizes fundamental concepts and experimental approaches for kinetic studies of organic matter thermal transformation, it provides an overview of modern methods, equipment and experimental procedures for obtaining bulk and compositional activation energy distributions (spectra) in open and closed systems, and discusses the benefits, limitations, and possible applications of the different methods.The paper presents the scope of experimental procedures, which have been elaborated at Skoltech, and the obtained results: (i) bulk kinetic spectra, which are aimed at express prediction of the total yield of mobile hydrocarbons during kerogen transformation; (ii) compositional kinetic spectra, which considers the amount and composition of hydrocarbon products; (iii) kinetic model of organic matter transformation in a closed system, which considers primary kerogen decomposition and secondary reactions of the hydrocarbons. The kinetic spectra were obtained for various organic-rich rocks collected within the Russian Federation.